FLIM-Phasor Analysis (FLIM-ϕ) of Aβ-Induced Membrane Order Alterations: Towards a Cell-Based Biosensor for Early Alzheimer’s Disease Diagnosis - Antonella Battisti; Maria Grazia Ortore; Silvia Vilasi; Antonella Sgarbossa (Micromachines)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder, and its early detection can be critical for a prompt intervention that can potentially slow down the disease progression and improve the patient’s quality of life. However, a diagnosis based solely on clinical symptoms can be challenging, especially in the early stages, while the detection of specific biomarkers such as amyloid-β peptide (Aβ) and tau proteins can provide objective evidence for diagnosis. In this work, we explored the effects of Aβ peptide on cell membrane properties thanks to fluorescence lifetime imaging (FLIM) combined with the phasor analysis (FLIM-ϕ). The results showed that the membrane viscosity is altered by the presence of Aβ peptide and that cells experience this effect even at nanomolar concentrations of peptide. This considerable sensitivity opens up the possibility of envisioning a cell-based biosensor able to detect very low concentrations of Aβ in a biological fluid, thus enabling timely diagnosis and intervention.